A chemical method of determining spoilage in fish - Atilano, Josefina B. (College of Fisheries, University of the Philippines, 1965)
Ever since the time when chemical analysis began to be applied to food, attempts have been made to find and use analytical procedure for a particular chemical substance or group of them, which would be accurate, reliable, specific and by which wholesome fresh, acceptable or passable foodstuff could be readily and easily distinguished from those considered to be unfit for consumption. Among the earliest was the use of the presence of ammonia in meat as an index of spoilage. Subsequently a variety of products have been suggested and tried as spoilage indicator. The ideal sought was still a method of procedure for a substance which would increase to a significant level when spoilage becomes evident or detectable by the senses. Furthermore this substance and the procedure for measuring it should be applicable to as many different kinds of the foodstuffs, as are in general use and to all the processed variation which may occur. In other words, the ideal procedure should be able to distinguish between fresh fish and that in its first stages of spoilage, regardless of species, processing treatment, storage conditions or any other factors which may be encountered. In addition the method should involve relatively simple apparatus, which will easily be assembled and dismantled for cleaning, and it should be quickly and readily carried out. It has been said on many occasions by many writers that no one universally applicable method is available to determine spoilage under all circumstances and that they thought no one ever will be found. For individual substances or group of similar ones, this is probably the case. Taking into account the diversity of bacterial flora and variety of fish products it is to be expected that any method dependent upon a particular type of bacterial activity will meet with failure a certain portion of time. However in this case of the Volatile Reducing (VRS) Method the situation is definitely different. Here a procedure has been designed to determine all types of volatile constituents which maybe present originally or produced in the fish through the spoilage process. It is generally agreed and accepted that when fish spoil, their odors increase an intensity. The VRS method measures this odor intensity. Meanwhile the marketing of fish becomes a race against time to bring the fish to the ultimate consumer before the quality is reduced below an acceptable level. However it is not the quality at the time the fish is acquired which is of importance but rather the quality at some future time when it is ultimately consumed. It was to this consideration that this paper sought to report the attempts in providing a workable scientific foundation on which to base the proposed scheme of grading fish for quality. On the other hand, newer objective tests and improvements in existing tests are developed and explored which might throw considerable new light on the biochemistry of spoilage.